Carotid body disease and the physician–chronic carotid glomitis. Issue 764 (June 1989) - Heath, D.; Khan, Q.; Nash, J.; Smith, P.
Abstract : There are three types of histological change in the carotid bodies which appear to have physiological and clinical associations. A prominence of the dark variant of chief cells with their contents of met-enkephalin and other peptides appears to be associated with acute exposure to hypoxia. Proliferation of sustentacular cells around the clusters of chief cells appears to be related to ageing and also to systemic hypertension. Recently we have described a new condition of chronic carotid glomitis which is characterized by follicles of lymphocytes and may have a basis in auto-immunity. In the present review we report for the first time plasma cell activity in the carotid bodies of an elderly man, especially around nerve fibrils and unmyelinated axons ensheathed in sustentacular cells. Such appearances are consistent with the view that ageing nerve fibrils may be the antigenic stimulus for the development of chronic carotid glomitis.